STUDI KRITIS TERHADAP JOVI ADHIGUNA SEBAGAI CONTENT CREATOR YANG BERGAYA ANDROGINI DI ERA GLOBALISASI - Ahmad Hidayah (Prodi S1 Ilmu Komunikasi, Fakultas Ilmu Sosial, Universitas Negeri Jakarta, 2021)
This article discusses the impact of the existence of content creators, especially Jovi Adhiguna, as a variety of subcultural careers in the era of globalization. This case study on Jovi Adhiguna is based on his existence as one of the representations of subcultures in Indonesia, interestingly, he has male sex but looks like a woman. This is known as the concept Androgyny. If it is related to the system of values ​​and norms that exist in Indonesia, such things have imbalances and even include violations in attitude and behavior in the midst of society. The purpose of this article is to determine the impact arising from the birth of subcultures as a result of the development of globalization in Indonesia on young people. From the results obtained, it is found that Jovi Adhiguna is an influential agent in conditions of the collapse of the existing value and norm systems in Indonesia, in this case the eastern culture.